2022
DOI: 10.1029/2021jb023451
|View full text |Cite
|
Sign up to set email alerts
|

3D GNSS Velocity Field Sheds Light on the Deformation Mechanisms in Europe: Effects of the Vertical Crustal Motion on the Distribution of Seismicity

Abstract: Crustal deformation in the Eurasian plate and its plate boundaries is the result of a variety of geological processes. These processes have two main origins: first, the far field tectonic convergence between the African plate and Stable Europe plus its local tectonic complexities associated with back-arc extension (e.g., Tyrrhenian, Aegean) or microplate motion (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 86 publications
1
16
2
Order By: Relevance
“…This pattern of vertical motions does not correlate well with the GNSS-derived vertical velocities of this study (Fig. 4b), or with that of Piña-Valdés et al (2022), which show subsidence for almost the entire Circum-Pannonia region. However, it is clear that the margins of the Pannonian basin are still relatively uplifting with respect to the deep basins, which means a near 0 vertical motion of the margins compared to the 1-2 mm/ yr subsidence of the basins in the ITRF reference frame (Fig.…”
Section: Vertical Velocitiescontrasting
confidence: 89%
See 2 more Smart Citations
“…This pattern of vertical motions does not correlate well with the GNSS-derived vertical velocities of this study (Fig. 4b), or with that of Piña-Valdés et al (2022), which show subsidence for almost the entire Circum-Pannonia region. However, it is clear that the margins of the Pannonian basin are still relatively uplifting with respect to the deep basins, which means a near 0 vertical motion of the margins compared to the 1-2 mm/ yr subsidence of the basins in the ITRF reference frame (Fig.…”
Section: Vertical Velocitiescontrasting
confidence: 89%
“…The scarce GNSS network of the region in the 2000's resulted in the interpolation of the velocity field based on a relatively crude dataset (Grenerczy et al 2005), which did not enable the reliable calculation of strain rate components, given the small gradients in surface velocities in the area. More recent GNSS-based studies successfully demonstrated the potential of geodetic strain analysis from a global (Kreemer et al 2014) or European scale (Piña-Valdés et al 2022) perspective. However, a targeted analysis of the Circum-Pannonian region is still lacking.…”
Section: Research Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to the present-day tectonic setting of the Alps, studies have shown a slow and complex deformation pattern in a global strike-slip context related to the rotation of Apulian plate (Mathey et al, 2021;Piña-Valdés et al, 2022). In this context, the internal part of the J o u r n a l P r e -p r o o f Alps has been subjected to extensional deformation since 3 Ma, whereas its external part still undergoes compression (Sue et al, 1999;Bilau et al, 2020), as shown by geodesy and seismicity (Walpersdorf et al, 2018;Mathey et al, 2021;Piña-Valdés et al, 2022). This deformation pattern is characterized by a shortening rate of ≤1 mm/yr (Nocquet et al, 2016) and vertical component culminating in the ECMs with rates > 1mm/yr (Serpelloni et al, 2013).…”
Section: Geological and Tectonic Settingsmentioning
confidence: 99%
“…East of the city of Nice, Bigot-Cormier et al (2004) analysed seismicreflection profiles to infer uplift rates of 0.3-0.5 mm/yr of the North Ligurian margin since 5 Ma. Regarding the present-day uplift, several studies using GPS data in the Alps (Serpelloni et al, 2013;Nocquet et al, 2016;Walpersdorf et al, 2018;Sternai et al, 2019;Piña-Valdés et al, 2022) evidence limited to slow vertical displacements of <0.5 mm/yr in the SW Alps.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%